2018
DOI: 10.3389/fgene.2018.00607
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of Selection in Admixed Dairy Cattle in Tanzania

Abstract: Multiple studies have investigated selection signatures in domestic cattle and other species. However, there is a dearth of information about the response to selection in genomes of highly admixed crossbred cattle in relation to production and adaptation to tropical environments. In this study, we evaluated 839 admixed crossbred cows sampled from two major dairy regions in Tanzania namely Rungwe and Lushoto districts, in order to understand their genetic architecture and detect genomic regions showing preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 73 publications
2
46
1
2
Order By: Relevance
“…Such a large geographic distribution may be consistent with known ancient migration and admixture events during dispersal of cattle out of the domestication center [17,18,20,[55][56][57][58][59][60][61] as well as more recent historical migrations between Asia and Europe and in the Mediterranean [27,62], although admixture phenomena among wild taurine and zebuine progenitors may not be ruled out. Interestingly, we found that several of the candidate genes on BTA14 (XKR4, TMEM68, TGS1, LYN, CHCHD7, SDR16C5, PENK, TOX, RPS20, PLAG1) had been previously reported to harbor signals of selection/association in taurine/zebuine composite populations or zebuine breeds [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. This evidence possibly supports the speculation that pigment-related gene variants and phenotypes in grey taurine cattle may represent a heritage of zebuine origin, despite the fact that, for PLAG1, an allele with major effects on body size, weight, and reproduction has been shown to be a >1000 year-old-derived allele that increased rapidly in frequency in Northwestern European B. taurus between the 16th and 18th centuries, and that was hence introgressed, towards the 19th and 20th centuries, into non-European B. taurus and Bos indicus breeds likely to increase the stature of modern cattle [79,80].…”
Section: Hair Greying: a Possible Zebuine Heritage In Taurine Cattle mentioning
confidence: 89%
“…Such a large geographic distribution may be consistent with known ancient migration and admixture events during dispersal of cattle out of the domestication center [17,18,20,[55][56][57][58][59][60][61] as well as more recent historical migrations between Asia and Europe and in the Mediterranean [27,62], although admixture phenomena among wild taurine and zebuine progenitors may not be ruled out. Interestingly, we found that several of the candidate genes on BTA14 (XKR4, TMEM68, TGS1, LYN, CHCHD7, SDR16C5, PENK, TOX, RPS20, PLAG1) had been previously reported to harbor signals of selection/association in taurine/zebuine composite populations or zebuine breeds [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. This evidence possibly supports the speculation that pigment-related gene variants and phenotypes in grey taurine cattle may represent a heritage of zebuine origin, despite the fact that, for PLAG1, an allele with major effects on body size, weight, and reproduction has been shown to be a >1000 year-old-derived allele that increased rapidly in frequency in Northwestern European B. taurus between the 16th and 18th centuries, and that was hence introgressed, towards the 19th and 20th centuries, into non-European B. taurus and Bos indicus breeds likely to increase the stature of modern cattle [79,80].…”
Section: Hair Greying: a Possible Zebuine Heritage In Taurine Cattle mentioning
confidence: 89%
“…Chinese indigenous cattle inhabit more extensive altitudes than yak, from low-altitude coastal regions to the Tibetan Plateau, and may provide a better model to explore the genetic basis of high-altitude adaptation. The selective signatures of SNPs have been explored extensively in cattle (Pérez O'Brien et al, 2014;Xu et al, 2015;Zhao et al, 2015;Cheruiyot et al, 2018) and other livestock (Wilkinson et al, 2013;Onzima et al, 2018). However, similar analyses of CNVs are still limited.…”
Section: Cnvs Revealed the Potential Molecular Basis To High-altitudementioning
confidence: 99%
“…Detection of selection signals associated with economic traits has been successfully implemented in several livestock species, such as cattle [ 35 ], pigs [ 36 ], sheep [ 37 ] and horses [ 38 ]. However, many approaches have been proposed to identify selection signals in genomes, such as Fst, XP-EHH and iHS.…”
Section: Discussionmentioning
confidence: 99%